Consent and Resistance: Indonesian Corona-Inspired Islamic Music in the Wake of the COVID-19 Pandemic - Lestari, Febriyanti (Universitas Islam Negeri Sunan Kalijaga, 2024)
The COVID-19 pandemic sparked the production of corona-inspired Islamic music in Indonesia. Interestingly, against the backdrop of chaos and uncertainty, the genre appears to have transcended mere value-added entertainment and can be viewed as a tool that operates with or against power. Using Stuart Hall's concept of culture and power, this study aims to examine how popular culture such as this is utilized by the elites and the ordinary. This is qualitative research using content analysis, and the data were taken from the lyrics and live performances of Bimbo with their song “Corona” and Audul Marom rebana group with “Sirahku Mumet Sirahmu Piye.” This research found that corona-inspired Islamic music is not just an aesthetic call to surrender to God in the face of crisis. Instead, it acts as a vehicle for cultural adaptation by authorities and a platform for expressing dissent among the ordinary. Bimbo’s “Corona” and its involvement in the government-sponsored fundraising concerts exemplify efforts to mitigate public distrust during the pandemic. In contrast, the “Sirahku Mumet Sirahmu Piye” reproduced and popularized by a local rebana group from Demak echoes the plight of the lower classes, articulating the economic burden of the commoners due to COVID-19 measures.